The Influence of Green Accounting and Social Responsibility on Firm Value in the Hotel Sector - Ni Putu Tia Miranthi; Komang Adi Kurniawan Saputra; I Dewa Ayu Eka Pertiwi (International Journal of Environmental, Sustainability and Social Science, 2026)
This study aims to analyze the effect of Green Accounting and Corporate Social Responsibility on Firm Value in the hospitality sector, specifically five-star hotels in Badung Regency. T. In the hospitality industry, the implementation of green accounting and corporate social responsibility programs plays an important role in building a positive image and enhancing stakeholder trust. This study employs a quantitative approach using multiple linear regression analysis. The population consists of hospitality companies in Badung Regency, with a total sample of 130 obtained through purposive sampling technique. The data used are secondary data analyzed using the Statistical Package for Social Science (SPSS) version 25.0. Hypothesis testing is conducted using partial tests (t-test) and simultaneous tests (F-test) to determine the effect of independent variables on the dependent variable. The results show that Green Accounting has a positive and significant effect on firm value. This indicates that better implementation of environmentally-based accounting practices leads to higher firm value, as reflected in investor perceptions and company performance. Furthermore, Corporate Social Responsibility also has a positive and significant effect on firm value. This finding suggests that companies actively implementing and disclosing CSR programs tend to have better reputations and higher levels of trust from the public and investors. Overall, this study implies that the implementation of green accounting and corporate social responsibility are important strategies in enhancing firm value, particularly in the hospitality industry which highly depends on image and environmental sustainability.